Fertility concerns, preservation strategies and quality of life in young women with breast cancer: Baseline results from an ongoing prospective cohort study in selected European Centers. (October 2019) - Ruggeri, M.; Pagan, E.; Bagnardi, V.; Bianco, N.; Gallerani, E.; Buser, K.; Giordano, M.; Gianni, L.; Rabaglio, M.; Freschi, A.; Cretella, E.; Clerico, M.; et al.
Abstract: Objectives: Most research addressing needs and concerns of young patients with breast cancer (≤40 years) is retrospective. The HOHO European protocol is a prospective multicenter cohort study of young women with newly diagnosed breast cancer, about fertility, psychosocial and quality of life concerns. Here we report the baseline data and focus on predictors of fertility concerns. Materials and methods: Patient surveys and medical record review were used. The baseline survey included sociodemographic, medical and treatment data as well as questions on fertility concerns and preservation strategies. Subscales from the CAncer Rehabilitation Evaluation System-Short Form (CARES-SF) were administered to measure specific quality of life aspects. Uni- and multivariable modeling were used to investigate predictors of greater fertility concern. Results: Among 297 eligible respondents, 67% discussed fertility issues before starting therapy, 64% were concerned about becoming infertile after treatment, and 15% decided not to follow prescribed therapies. Fifty-four percent of women wished future children before diagnosis; of these, 71% still desired biologic children afterwards. In multivariable analysis, not having children was the only patient characteristic significantly associated with fertility concerns at diagnosis. Twenty-seven percent used fertility preservation strategies. Women who received chemotherapy reported greater physical (p = 0.021) and sexual difficulties (p = 0.039) than women who did not. Women who were married or had a partner reported less psychosocial problems than single women (p = 0.039). Conclusions: Young women with newly diagnosed breast cancer have several concerns, including, but not limited to, fertility. The HOHO European study provides valuable information to develop targeted interventions. Highlights: Many young women desire future biologic children after breast cancer. Sixty-four percent of study patients had fertility concerns. A low proportion of patients took fertility preservation measures. Women treated with chemotherapy reported greater physical and sexual difficulties. Women with stable relationships reported less psychosocial problems than single women.